Penerapan Metode Al-Sima’a wa Al-Muhafadzah Terhadap Penguasaan Mufradat Bahasa Arab Siswa Kelas XI MA Amanatul Ummah (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to describe the implementation of the Al-Simaa’ wa Al-Muhafadzah method in Arabic vocabulary learning and to analyze its effectiveness in improving students’ mastery of mufradat at grade XI of MA Amanatul Ummah. The research background arises from the challenges faced by students in acquiring sufficient vocabulary, which are caused by the limitations of traditional teaching methods, low motivation, and restricted time allocation for Arabic language lessons in madrasahs. The Al-Simaa’ wa Al-Muhafadzah method, which emphasizes listening (al-simā‘) and memorizing (al-muḥāfaẓah), is considered relevant to overcome these issues. This study applied a quantitative approach with a quasi-experimental design. The research subjects consisted of 30 students, and the instruments included vocabulary tests (pre-test and post-test), observation sheets, and questionnaires. Data were analyzed using paired sample t-tests and descriptive analysis. The findings revealed a significant improvement in students’ vocabulary mastery after the implementation of the Al-Simaa’ wa Al-Muhafadzah method. The average score increased from 55.3 in the pre-test to 78.6 in the post-test, with the t-test showing a significant difference (t = 8.92; p < 0.05). Classroom observations also indicated an increase in students’ active participation, while the questionnaire results showed that 80% of students found it easier to remember vocabulary through listening and repetition. However, some students still required visual aids to better understand word meanings. Therefore, it can be concluded that the Al-Simaa’ wa Al-Muhafadzah method is effective in enhancing Arabic vocabulary mastery, as well as fostering students’ motivation and self-confidence. It is recommended that this method be applied continuously and integrated with visual media to accommodate diverse learning styles.